Murder hornets - Jaycox, Jaclyn, 1983- (2023)
"Murder hornets are big! They are the largest hornet on Earth. Also called Asian giant hornets, these fierce insects will eat bees and wasps. Young readers can get all the facts with easy text and exciting photos"--
Includes bibliographical references and index.
Ages 5-8
Grades K-1
Keywords: Hornets -- Juvenile literature